The Moderating Role of Digital Transformation on the Influence of Workplace Spirituality and Sustainable Leadership on School Organizational Performance - Yuliana Sri Purbiyati; Richard Andrew (International Journal of Applied Business and International Management, 2025)
Educational institutions increasingly face pressure to improve organizational performance amid changing stakeholder expectations and rapid digitalization. This study examines the moderating role of digital transformation in the relationships between workplace spirituality, sustainable leadership, and organizational performance. Using Partial Least Squares–Structural Equation Modeling (PLS-SEM), data were collected from school leaders and unit heads at educational institutions in Indonesia. The results indicate that workplace spirituality has a significant positive effect on organizational performance (? = 0.842; p 0.001), while sustainable leadership does not show a significant direct influence (? = –0.225; p 0.05). Digital transformation also has a positive direct effect on organizational performance (? = 0.288; p 0.05), but does not moderate the relationships between workplace spirituality or sustainable leadership and organizational performance. These findings indicate that school performance is primarily shaped by value-based and relational factors, with digital transformation contributing independently as a supportive capability. Practically, schools should strengthen human-centered values while aligning digital initiatives with institutional practices. Theoretically, digital transformation operates as a complementary capability rather than altering the influence of leadership or workplace spirituality.